Brazilian social fears - de Freitas, Maria Ester; dos Reis, José Marcelo Dantas (Organizações & Sociedade, 2014)
This paper analyzes what are the fears of Brazilians, from an empirical study conducted in São Paulo and Salvador, involving 1380 direct interviews. The results are interpreted through the lens of historical and social psychological perspectives. We assume that in an increasingly interdependent world, the knowledge of the behavior of a people and the reasons for this behavior can help us understand the choices, values , decisions and interactions that affect the social life, the universe of private organizations and the public administration. In a more prosperous context as the current, Brazilians are more relaxed and confident in the future?